Yakitate!! Japan 2 - Hashiguchi, Takashi (San Francisco : Viz Media, 2006)
Budding bakers Kazuma and Kawachi prepare for their first assignment at Pantasia's South Tokyo branch, but their afro-sporting manager's initial challenge is anything but a piece of cake--they must create French bread that not only tastes good to humans, but to horses as well. Kazuma's used to baking unusual bread for tough customers, but how on earth is he going to come up with some equine edibles that transcend the boundaries of taste and species?!
"First published by Shogakukan Inc. in Japan as Yakitate!! Japan."
"New and adapted artwork and text."
Keywords: Comic books, strips, etc. -- Japan; Graphic novels; Young adult fiction